Pengelolaan Perpustakaan Di Sekolah Dasar (Studi Situs Sekolah Dasar Al Firdaus Surakarta) - Rohayati, Suci, Dr. Sofyan Anif, M.Si, Dr. Jalal Fuadi, M.M (2017)
This study have four aims to describes: 1) provision of reading materials and reference of library, 2) Activity circulation reading materials at the library, 3) literacy activities at the library, and 4) satisfaction of visitors to the library in Al Firdaus Elementary Schools of Surakarta. This research is qualitative research with etnography design. Data was collected by observation, interview, and documentation. Data validation was done with reference to the credibility, transferability, dependability, and confirmability. Data analysis use interactive model analysis. Results of this research there are four things about: 1) Procurement of reading material and reference library begins with coaching principals to library personnel to be responsible for the election and appointment of library materials and can work with teachers in defining and selecting a collection of reading materials and reference. Procurement of reading material and references obtained from donations and purchases. 2) Activity circulation of reading materials begins with conducting an inventory, cataloging, classification tenths of DDC, completion and preparation on the bookshelf. Services that are used are already using Digital Library system. Loan collections in accordance with the regulations and the late return of library sanctions. 3) Literacy activities 'Likes to Read Books program ' performed daily by division: 1st-3rd weeks for grade I and III, and 4th-6th weeks for grade IV and VI for an hour before Indonesian lesson starts. 4) Satisfaction of visitors to library at the Al Firdaus Surakarta Elementary School can be seen and measured on the completeness of the collection of reading material and reference, the services provided by the library staff, the amount of borrowing books annually, the facilities available in the library, and the availability of internet accessible computers to help students find references that do not exist in the library.